Estimation of Some Heavy Metals Concentration in Potato Chips Samples - Al Khansa Saeid; Nuha Khalaefa; Gamal Aboulgasem (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. This study was conducted to determination of concentration of some heavy metals (cd, fe) in potato chips samples due to essential or toxic nature of this metals and due to increase consumption of potato chips especially by children. Methods. In the present work, the level of cadmium and Iron in some potato chips samples from Libyan markets were determined by: Flame and graphite furnace atomic absorption spectrophotometry thermo GF95), Germany. Results. The study recorded presence of this heavy metals in all samples in different concentrations. Cadmium concentration ranged from 0.2950 mg/l to 1.8300 mg/l, whereas iron concentration ranged from 17.5767 mg/l to 32.1390 mg/l. All samples contained heavy metals in different concentrations. Some of these metals are present in high concentration especially cadmium and iron. Conclusion. The results showed that some samples contain these metals in a percentage above the permissible limit, this exposes consumers of these products to the risk of developing serious health problems such as cancer. Cite this article. Saeid A, Khalaefa N, Aboulgasem G. Estimation of Some Heavy Metals Concentration (Fe, Cd) in Potato Chips Samples. Alq J Med App Sci. 2022;5(2):493-497. https://doi.org/10.5281/zenodo.7191143